Visualisasi Karya Patchwork Sebagai Usaha Penyadaran Menjaga Kelestarian Lingkungan - Centaury Harjani (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2016)
The work of art has a lot of variety, concepts, themes, until the destination in the making art. The sameness in every work of art that each work must have had the mark or the symbolism that will be showed through the work. This paper contains the elaboration of a work textile craft "Dryness" based on material, technique and visual aspects ofform in order to preserving the environmental awareness. "Dryness" is the work of art that use residue material which isnot commonly used in a work of textile craft, it is to influencing the behavior of people generaly. Creating the works using patchwork and embroidery as a whole is intended to describe the environmental conditions of drought. This works not only have meaning to raise awareness of natural conditions in the environment, but also condering people about how it impacts the environment and how it impacts to everyone who witnessed it. The expectation from this article is inspire the creation of art to have insight environmental awareness not only in terms of a visual aspect but also from the material aspect.Keywords: Visualization, Environmental Awareness, Patchwork.